Evaluation of axial length measurements obtained using three different techniques- applanation A-scan, immersion A-scan and optical biometer - Arora, Chandni; Gupta , Surbhi (International Journal of Research in Medical Sciences, 2023)
Background: To compare measurements of axial length obtained with manual A-scan, immersion A-scan and optical biometer and assess the accuracy of different techniques of intraocular lens power calculation. Methods: This was a prospective randomized study done in 90 patients over a period extending from November 2019 to October 2020 in the upgraded department of ophthalmology, Government Medical College Jammu. Intraocular lens power was calculated by measuring axial length by three different techniques and further the accuracy of the axial length values obtained were compared. Results: In this study, mean axial length measured by applanation A-scan was 22.86±0.85 mm which ranged from 20.99-24.6 mm and axial length measured by immersion technique ranged from 21.5-24.9 mm with a mean AL of 22.92±0.85 mm. AL measured by non-contact method ranged from 20-25.08 mm with a mean AL of 23.1±0.93 mm. There was a statistically significant difference between all the three techniques regarding the measured AL (p=0.0004). Conclusions: This study concludes that the optical biometry has greater accuracy than ultrasound biometry including applanation and immersion A-scan.